63 Stepping up for operation moonshot – mass spectrometry testing for COVID 19. (15th December 2021) - Heales, Simon; Aitkenhead, Helen; Burke, Derek; Haidri, Sehrish; Metcalf, Carol; Belsten, Jack; Ghansah, Nana
Abstract : In September 2020, the UK government announced Operation Moonshot; the remit being to increase testing capacity for COVID 19. Amongst the diagnostic platforms to be considered was mass spectrometry. To facilitate this, the Department of Health and Social Care (DHSC) brought together and funded academic mass spectrometry (P1) and specialist NHS laboratories (P2) across the UK. With regards to the latter, the GOSH Enzyme Lab and the Neurometabolic Unit (National Hospital) were identified as a P2 grouping that would collaborate with the mass spectrometry unit at the UCL Institute of Child Health (P1 – Head Prof K Mills). This P1 lab developed a unique proteomic approach to measure diagnostic proteins associated with the SARS-CoV-2 virus. This method was transferred over to our NHS labs for full validation. Rapid progress was made and the DHSC identified us as a 'vanguard lab'. Within 6 months of commencement of the project, a validated method was developed that had excellent agreement with PCR testing. Our data was used in presentations throughout the DHSC and for briefing of government ministers. Despite the pressures of the pandemic, our NHS staff went above and beyond to deliver on time. Furthermore, close working with an academic partner provided a proof of principle example whereby state of the art mass spectrometry-based methods can successfully be translated across into the NHS environment.